2021
DOI: 10.3390/diagnostics11112093
|View full text |Cite
|
Sign up to set email alerts
|

Faecal Haemoglobin Estimated by Faecal Immunochemical Tests—An Indicator of Systemic Inflammation with Real Clinical Potential

Abstract: Multimorbidity is the major cause of ill-health and premature death in developed countries. The ability to identify individuals at risk of developing chronic disease, particularly multimorbidity, reliably, and simply, and to identify undiagnosed disorders, is vital to reducing the global burden of disease. This narrative review, the first of recent studies, demonstrates that raised faecal haemoglobin concentration (f-Hb) is associated with increased all-cause and cause-specific mortality and with longer-term c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…It is difficult to clearly explain the FIT (+) but colonoscopy negative group. We inferred that this finding may indicate systemic inflammation, as previously described [9]. Therefore, this study started with the assumption that the FIT (+) group would differ from the FIT (−) group, as they could potentially represent subclinical inflammation.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…It is difficult to clearly explain the FIT (+) but colonoscopy negative group. We inferred that this finding may indicate systemic inflammation, as previously described [9]. Therefore, this study started with the assumption that the FIT (+) group would differ from the FIT (−) group, as they could potentially represent subclinical inflammation.…”
Section: Discussionmentioning
confidence: 81%
“…Nonetheless, Libby et al [30] and Chen et al [13] have indicated that occult blood in faeces could predict an increase in mortality that is not accounted for CRC among national health-examination recipients, probably representing a generalised inflammatory status. This is also highlighted by a number of studies that have demonstrated an association between positive FIT and the risk of developing chronic disorders, raising a possibility that FIT abnormality, without gross abnormal mucosal lesions, could be an indicator of subjects that are at risk of chronic diseases mirroring heightened inflammation [9]. In the present study, we classified participants undergoing FIT in a national CRC screening programme into FIT (+) and FIT (−) groups and compared the incidence of IMIDs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is interesting that this association with deprivation is shared by screening and symptomatic patients. In the review by Barnett et al, 39 they hypothesise that an elevated systemic inflammatory response (SIR) may explain the higher f-Hb concentrations observed in the absence of colorectal pathology, in screener participants with chronic conditions (ischaemic heart disease, cerebrovascular disease, diabetes and hypertension) and on certain medications (PPIs and anticoagulants). Perhaps a heightened SIR is one confounding variable which may link deprivation, co-morbidity and a raised f-Hb in the absence of colorectal pathology.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, recent studies have shown that detectable f-Hb is associated with increased all-cause and cause-specific mortality, and with longer-term conditions including diabetes, hypertension, cardiovascular disease and psoriasis, and with probable intake of particulate matter. 25 All of these conditions are associated with systemic inflammation. In consequence, the suggestion has been made that elevated f-Hb has considerable potential to identify individuals at risk of, or who already suffer from, early stage, undiagnosed, chronic disease.…”
mentioning
confidence: 99%